Relationship between benzene concentration, MDA levels and kidney function in car painting workshops in Surabaya: a cross-sectional observational study - Tualeka, Abdul Rohim; Aziz, Mohd Yusmaidie; Perumal, Velu; Thamaraikani, Tamilanban; Rosnon, Roslan; Novianti, Salsabila; Rahmawati, Pudji; Ahsan, Ahsan (Taylor and Francis, 2024)
Background: Car painting workers are at risk because of the use of solvents containing benzene as the main ingredient in the car painting process. One of the clinical effects of systemic benzene is kidney disorders. Therefore, the purpose of this study is to analyze the relationship between benzene and Risk Quotient (RQ) benzene concentrations with Malondialdehyde (MDA), Blood Urea Nitrogen (BUN), and creatinine levels in workers exposed to benzene in car painting workshops in Surabaya. Methods: This is an observational, cross-sectional study conducted at two car painting workshops in Surabaya that use benzene as a solvent in their production process, namely in industries in Kalijudan and Jemursari. The research sample was taken using the accidental sampling method and as many as 30 respondents were involved in this study. The variables studied included benzene concentration, RQ benzene, MDA levels, and kidney function (BUN and creatinine levels). Analysis of the data used is a descriptive and bivariate analysis using the Pearson correlation test. Results: There was no significant relationship between concentrations, RQ benzene, and MDA levels in workers in painting in Surabaya (p> 0.05). There was no significant relationship between benzene concentration, BUN levels, and creatinine levels in paint workers in Surabaya (p> 0.05). There was no significant relationship between benzene RQ and BUN and creatinine levels in paint workers in Surabaya (p> 0.05). Conclusions: The results of this study indicate that the effects of benzene do not lead to impaired kidney function. The benzene RQ variable in this study did not become a determining factor in BUN and creatinine levels in workers.